Eosinophils count in peripheral circulation is associated with coronary artery disease. (July 2019) - Gao, Shanshan; Deng, Yangyang; Wu, Jun; Zhang, Lisha; Deng, Fuxue; Zhou, Juan; Yuan, Zuyi; Wang, Lijun
Abstract: Background and aims: Allergic asthma can accelerate atherosclerosis, a disease in which plaque is deposited onto arterial walls and that may lead to coronary artery disease (CAD). Eosinophils are the most important effector cells in allergic asthma and are likely to become novel biomarkers for risk stratification of patients with CAD, but the relationship between eosinophil count and CAD remains unclear. We aimed to evaluate this relationship and the use of eosinophils in predicting CAD. Methods: A total of 5287 patients who underwent coronary angiography were recruited. Their biochemical parameters, including eosinophil count, were measured and their correlation with the severity of coronary artery stenosis, as quantified by the Gensini score system, was evaluated. Results: The percentages of eosinophils in leukocytes (PELs) were lower in CAD patients ( p  < 0.001), and had a significant negative correlation with Gensini scores ( r  = -0.112, p  < 0.001). PELs were also significantly lower in acute myocardial infarction patients ( p  < 0.001). After adjusting for baseline differences, low PELs remained strongly associated with severe CAD and acute coronary arterial thrombotic event. Receiver-operating characteristic curve analysis showed that combining PELs with traditional risk factors in predictive models for CAD severity (z = 4.470, p  < 0.001) or acute coronary arterial thrombotic event (z = 9.435, p  < 0.001) improved the predictive capabilities of those models. Conclusions: PELs, at least in patients undergoing coronary angiography, may be strongly related to the subtype and severity of CAD and, therefore, eosinophil count may be an accurate and independent biomarker to predict CAD severity and acute coronary arterial thrombotic events. Graphical abstract: Image 1 Highlights: A total of 5287 patients who underwent coronary angiography were included in the study. The eosinophil count may be strongly negativly related to the subtype and severity of CAD. Eosinophils may be a promising biomarker that can accurately and independently predict CAD severity and myocardial infarction.